Twenty years of experience with perineal injury in children - Bakal, U.; Sarac, M.; Tartar, T.; Cigsar, E. B.; Kazez, A. (Springer Heidelberg, 2016)
The aim of this study was to review our 20 years of experience determining the common mechanisms of perineal trauma and initial management to evaluate the effects of classification for treatment. A total of 75 children with perineal injuries were reviewed retrospectively, including patient demographics, mechanism of injury, associated injuries, injury severity score, presenting symptoms and methods of diagnosis and treatment. Amongst the 75 children (55 females and 20 males; mean age, 8 years), fall from height, followed by motor vehicle crash and sexual abuse were the most common reasons for injury. The most common symptom on presentation was bleeding, followed by abdominopelvic pain and tenderness. Eleven patients were allowed to heal secondarily, and 64 were examined under general anaesthesia. The affected area was repaired in 48, further diagnostic tools were needed in 20 and 11 cystoscopic, 10 rectoscopic, and 5 vaginoscopic evaluations were performed. Six patients with full-thickness injuries that extended to the peritoneum were treated with colostomy, and all were victims of motor vehicle crashes. The genital injury score is a useful genital trauma scale for predicting anogenital injury severity. Identifying the mechanism and severity of perineal and associated injuries under general anaesthesia may facilitate appropriate classification and management.
Keywords: Perineal injury; Falls; Motor vehicle crashes; Sexual abuse; Children